2021
DOI: 10.1097/jsm.0000000000000959
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure for the Sport Concussion Assessment Tool Symptom Scale in Adolescents After Concussion

Abstract: Objective:To examine the factor structure of the Sport Concussion Assessment Tool-5 (SCAT5) symptom scale in adolescents on their initial presentation to a concussion clinic within the typical recovery period after concussion (ie, <30 days). We hypothesize that the SCAT5 symptoms represent various clinically meaningful groups. A secondary purpose was to examine the effects of sex on the factor structure of the SCAT5 symptom scale.Study Design:Retrospective cross-sectional analysis.Setting:Tertiary, institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“… 64 , 67 , 103 This is further seen through the factor analysis of SCAT5 symptoms, in which individuals with higher symptom scores related to the Mental Health domain are associated with a longer time between injury and assessment. 3 While 1 in 3 individuals will eventually seek treatment for their mental health condition, 95 , 98 the initial evaluation is often delayed from the initial onset of symptoms. On average, individuals with a mood disorder will delay treatment for 8 years, while those with an anxiety disorder will delay for 9 years.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 64 , 67 , 103 This is further seen through the factor analysis of SCAT5 symptoms, in which individuals with higher symptom scores related to the Mental Health domain are associated with a longer time between injury and assessment. 3 While 1 in 3 individuals will eventually seek treatment for their mental health condition, 95 , 98 the initial evaluation is often delayed from the initial onset of symptoms. On average, individuals with a mood disorder will delay treatment for 8 years, while those with an anxiety disorder will delay for 9 years.…”
Section: Discussionmentioning
confidence: 99%
“…Factor weightings were extracted from studies that performed exploratory factor analysis on SCAT symptom scores 3 , 5 or reported symptom domain groupings. 8 , 61 These factor weightings were used to calculate factor scores for all participants, 44 following the 3-factor (Migraine Fatigue, Affective, Cognitive-Ocular), 5 4-factor (Physical/Somatic, Insomnia/Sleep, Emotional, Cognitive), 8 , 61 and 5-factor (Energy, Mental Health, Migrainous, Cognitive, Vestibulo-ocular) 3 schemes. Using SPSS 27.0, we ran 2-way analyses of variance for each factor, investigating whether the factor scores were significantly different between mental health conditions, and between the control and condition subgroups.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations